A novel class of cardioprotective small-molecule PTP inhibitors. (January 2020) - Antonucci, Salvatore; Di Sante, Moises; Sileikyte, Justina; Deveraux, Jordan; Bauer, Tyler; Bround, Michael J.; Menabò, Roberta; Paillard, Melanie; Alanova, Petra; Carraro, Michela; Ovize, Michel; Molkentin, Jeffery D.; et al.
Graphical abstract: Abstract: Ischemia/reperfusion (I/R) injury is mediated in large part by opening of the mitochondrial permeability transition pore (PTP). Consequently, inhibitors of the PTP hold great promise for the treatment of a variety of cardiovascular disorders. At present, PTP inhibition is obtained only through the use of drugs (e.g. cyclosporine A, CsA) targeting cyclophilin D (CyPD) which is a key modulator, but not a structural component of the PTP. This limitation might explain controversial findings in clinical studies. Therefore, we investigated the protective effects against I/R injury of small-molecule inhibitors of the PTP (63 and TR002) that do not target CyPD. Both compounds exhibited a dose-dependent inhibition of PTP opening in isolated mitochondria and were more potent than CsA. Notably, PTP inhibition was observed also in mitochondria devoid of CyPD. Compounds 63 and TR002 prevented PTP opening and mitochondrial depolarization induced by Ca 2+ overload and by reactive oxygen species in neonatal rat ventricular myocytes (NRVMs). Remarkably, both compounds prevented cell death, contractile dysfunction and sarcomeric derangement induced by anoxia/reoxygenation injury in NRVMs at sub-micromolar concentrations, and were more potent than CsA. Cardioprotection was observed also in adult mouse ventricular myocytes and human iPSc-derived cardiomyocytes, as well as ex vivo in perfused hearts. Thus, this study demonstrates that 63 and TR002 represent novel cardioprotective agents that inhibit PTP opening independent of CyPD targeting.